The Mildenhall Treasure : a first-hand account - Lethbridge, T. C.
Introducing our articles by Richard Hobbs and Paul Ashbee (ANTIQUITY 71: 63Ð76) on the Mildenhall Treasure, the mass of Roman silverware which came to light in east England in 1946, I remarked that the principals are deceased. One principal did leave a first-hand account which has not been known before Ñ Tom Lethbridge, Hon. Keeper of Anglo-Saxon antiquities in the Museum of Archaeology and Anthropology, University of Cambridge. This extract from his unpublished autobiography is printed with the kind permission of Mrs Tom Lethbridge.